2018
DOI: 10.1111/ijcp.13094
|View full text |Cite
|
Sign up to set email alerts
|

Very long-term outcome of schizophrenia

Abstract: The long-term outcome of schizophrenia is highly variable, depending on access to mental healthcare, early detection of psychosis and pharmacological treatment. Recent data support the effectiveness of low-dose antipsychotic treatment for long-term maintenance in some patients. A proportion of first-episode schizophrenia patients, perhaps 20%, do not need long-term maintenance antipsychotic treatment. That proportion may be higher in schizophrenia spectrum patients. The reasons why these patients do not need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…In the cluster with generalized and severe deficit (Cluster 3) one of the most impaired domains was verbal memory, and as expected in first episodes, this group was the least represented in the whole sample. The small representation of the sample in this cluster was expected, since the subjects are at the early stages of their illness, and are not affected by the collateral effects of the course of the illness (Volavka and Vevera, 2018). The longitudinal stability of cognitive cluster subtypes becomes later, with the trajectory of the disorder (Heinrichs et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the cluster with generalized and severe deficit (Cluster 3) one of the most impaired domains was verbal memory, and as expected in first episodes, this group was the least represented in the whole sample. The small representation of the sample in this cluster was expected, since the subjects are at the early stages of their illness, and are not affected by the collateral effects of the course of the illness (Volavka and Vevera, 2018). The longitudinal stability of cognitive cluster subtypes becomes later, with the trajectory of the disorder (Heinrichs et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in some studies, a large proportion of patients, ranging from 19% (Moilanen et al, 2016) to 48.2% (Kua et al, 2003), were not on medication at the time of evaluation. In a recent review on the long-term outcome of schizophrenia, it was found that about 20% of first-episode patients do not need long-term maintenance antipsychotic treatment, and that this proportion may be higher in schizophrenia spectrum patients (Volavka & Vevera, 2018). Still, a large proportion of patients need indefinite maintenance antipsychotic treatment, and this would better be a low-dose regimen, as supported by the Moilanen et al (2016) study.…”
Section: Data On Medicationmentioning
confidence: 99%
“…However, some patients had extended periods of recovery, and, contrary to the commonly held view, patients with schizophrenia were not characterized by a progressive decline. More recently, Volavka and Vevera [24] concluded that symptomatic remission in long-term follow-up studies ranged between 16.4% in never-treated patients to 37.5% in patients who received antipsychotics. Better outcomes were associated with early detection and treatment of the first episode, and continuous psychosocial support over subsequent years [24].…”
Section: Introductionmentioning
confidence: 99%